The Effect Of Debt-Based Financing And Equity-Based Financing On Islamic Banks Profitability In Indonesia - Wahyudi, Rofiul; Diniyya, Aulia Arifatu; Satyarini, Julia Noermawati Eka; Mutmainah, Lu’liyatul; Maulida, Sri (Faculty of Islamic Economics and Business of Institut Agama Islam Negeri (IAIN) Pekalongan, 2020)
This study's main objective is to investigate equity-based financing and debt-based financing of the profitability of Islamic banking in Indonesia. This research is expected to contribute to the theoretical and practical dimensions. On the conceptual aspect, this study can provide evidence of whether equity-based financing and debt-based financing affect the profitability of Islamic banking. While on the practical dimension, Islamic banks in Indonesia can determine the extent of their profitability and, in turn, the competitiveness of Islamic banks to enable it to be developed in line or even better than conventional banks. The data analysis technique uses panel data regression, which is time series data and cross-section. Next, to estimate the panel data model, which is divided into three, namely: common effect, fixed effect, and random effect. The result of this study that partially equity-based financing does not affect ROE. At the same time, debt-based financing influences the ROE of Islamic banks. Partially equity-based financing and debt-based financing do not affect ROA of Islamic banks. However, it simultaneously shows that the independent variable test results, namely equity-based financing and debt-based financing, have a strong influence on the dependent variable, namely, profitability as measured by ROA and ROE.